PP.17.12: COMPARISON OF TWO VALIDATED DEVICES FOR AMBULATORY BLOOD PRESSURE MONITORING UNDER STATIC CONDITIONS. (June 2015) - Lazaridis, A.; Sarafidis, P.; Imprialos, K.; Georgianos, P.; Avranas, K.; Doumas, M.; Protogerou, A.; Athyros, V.; Karagiannis, A.
Abstract : Objective: Mobil-O-Graph and Spacelabs 90217 are two validated devices for ambulatory blood pressure (BP) monitoring. A thorough search of the literature revealed only one previous study comparing the two devices. In the present study we aimed to compare the values of systolic blood pressure (SBP) and diastolic blood pressure (DBP) measured by these devices under static conditions. Design and method: We studied 40 healthy volunteers aged 18–30 years, who were randomized in two groups. In both groups, two BP measurements with a mercury sphygmomanometer were initially performed. These intended to minimize the white-coat phenomenon and were not included in the analysis. Subsequently, in group A, two BP measurements with the Spacelabs device were performed followed by two measurements with a mercury sphygmomanometer and two with the Mobil-O-Graph device. Between every measurement, an interval of two minutes was applied. In group B the same procedure was followed but with a reverse order: Mobil-O-Graph, mercury sphygmomanometer, Spacelabs device. Results: Systolic BP values recorded with Mobil-O-Graph and Spacelabs did not differ significantly (Mobil-O-graph: 117.1 ± 9.8 mmHg, Spacelabs: 117.2 ± 10.3 mmHg, p = 0.943). SBP values obtained from both devices were not significantly different from those recorded with the mercury sphygmomanometer (117.8 ± 11.1 mmHg, p = 0.753 compared to Mobil-O-graph, p = 0.791 compared to Spacelabs). Similarly, no significant difference was observed regarding DBP measurements recorded with the two devices (Mobil-O-graph: 74.1 ± 9.4 mmHg, Spacelabs: 73.3 ± 9.4 mmHg, p = 0.611), as well as between any device and the mercury sphygmomanometer (72.0 ± 9.7 mmHg, p = 0.331 compared to Mobil-O-graph, p = 0.544 compared to Spacelabs). Values of SBP and DBP obtained with the two devices displayed strong correlations between them. Bland-Altman plots for SBP and DBP showed acceptable agreement between the two devices and no evidence of systemic bias. Conclusions: This study suggests that there is acceptable agreement in SBP and DBP measurements recorded with the Mobil-O-Graph and Spacelabs device under static conditions.